Fenomena Penggunaan Shopee Paylater: Dampak Gaya Hidup Hedonisme Sebagai Pemicu Perilaku Konsumtif Masyarakat Kota Binjai - Nadhira, Syazwina Nadhira; Barus, Elida Elfi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The development of financial technology has introduced various digital payment innovations, including the Buy Now Pay Later (BNPL) feature provided by Shopee Paylater. This study aims to analyze the influence of Shopee Paylater usage and a hedonic lifestyle on the consumptive behavior of the people in Binjai City. This research is quantitative with a causal associative approach. Data were collected through a survey of 150 respondents in Binjai City, selected via purposive sampling with criteria including active Shopee Paylater users. The analytical method used is multiple linear regression processed through SPSS. The results show that Shopee Paylater usage has a significant positive effect on consumptive behavior, driven by ease of access and low "pain of paying." Furthermore, a hedonic lifestyle, characterized by the pursuit of instant gratification and social prestige, acts as a primary trigger for excessive and unplanned spending. Simultaneously, both variables explain 64.2% of the variance in consumptive behavior. This study concludes that the digital credit phenomenon in Binjai City creates a psychological trap where desires are prioritized over needs. Recommendations include enhancing digital financial literacy for the Binjai community to prevent debt traps and ensuring more responsible credit management aligned with Islamic economic ethics.